EFFECTS OF CREDIT REFERENCE BUREAU PROCEDURES ON PERFORMANCE OF LOAN PORTFOLIO: A CASE OF SELECTED COMMERCIAL BANKS IN TANZANIA - BWANA, Kembo M.; MOSES, Baleke (Journal of European Economy, 2024)
This study investigates the impact of credit reference bureau (CRB) procedures on the performance of loan portfolios at selected commercial banks in Tanzania. A cross-sectional research design was adopted, with data collected through questionnaires and interviews involving 95 respondents from selected commercial banks. The findings show that the procedure to accessing loans had a positive and significant relationship with loan portfolio performance at these banks (β = 0.835, p = 0.000), as did loan approval procedures (β = 0.789, p = 0.001) and quality control procedures (β = 0.768; p = 0.002). All were significant at 5% level. The study concludes that using credit reference bureau services allows banks and other credit providers to assess potential clients, track their financial performance, and manage any accumulated debts. The study recommends that the government of Tanzania work closely with listed commercial banks and other financial institutions to ensure compliance with legal requirements specifically policies and procedures that assist in screening and monitoring clients from the initial stage of lending by using credit reference bureau procedures to improve decisions on loan provision. JEL: G21, D82, O55.